Nationwide Initiation of Cardiovascular Risk Treatments During the COVID-19 Pandemic in France: Women on a Slippery Slope? - Gabet, Amélie; Grave, Clémence; Tuppin, Philippe; Lesuffleur, Thomas; Guenancia, Charles; Nguyen-Thanh, Viêt; Guignard, Romain; Blacher, Jacques; Olié, Valérie (Frontiers in Cardiovascular Medicine, 2022)
Objectives This study examines the initiation of prescribed medication treatments for cardiovascular risk (antihypertensives, lipid-lowering drugs, oral anticoagulants in atrial fibrillation, and smoking cessation medications) during the COVID-19 pandemic in the French population. Methods For each year between 2017 and 2021, we used the French National Insurance Database to identify the number of people with at least one reimbursement for these medications but no reimbursement in the previous 12 months. We computed incidence rate ratios (IRRs) between 2017–2019 and, respectively 2020 and 2021 using Poisson regression adjusted for age and 2017–2019 time trends. We recorded the number of lipid profile blood tests, Holter electrocardiograms, and consultations with family physicians or cardiologists. Results In 2020, IRR significantly decreased for initiations of antihypertensives (−11.1%[CI95%, −11.4%;−10.8%]), lipid-lowering drugs (−5.2%[CI95%, −5.5%;−4.8%]), oral anticoagulants in atrial fibrillation (−8.6%[CI95%, −9.1%;−8.0%]), and smoking cessation medications (−50.9%[CI95%, −51.1%;−50.7%]) compared to 2017–2019. Larger decreases were found in women compared to men except for smoking cessation medications, with the sex difference increasing with age. Similar analyses comparing 2021 to 2017–2019 showed an increase in the initiation of lipid-lowering drugs (+ 11.6%[CI95%, 10.7%;12.5%]) but even lower rates for the other medications, particularly in women. In addition, the 2020 number of people visiting a family physician or cardiologist decreased by 8.4 and 7.4%. A higher decrease in these visits was observed in those over 65 years of age compared to those under 65 years of age. A greater use of teleconsultation was found in women. Conclusion The COVID-19 pandemic heavily impacted the initiation of medication treatments for cardiovascular risk in France, particularly in women and people over 65 years.